Capillary haemangioma on the palate: a diagnostic conundrum. (16th February 2016) - Singh, Pooja; Parihar, Anuj Singh; Siddique, Sana Noor; Khare, Pooja
Abstract : Haemangiomas are benign tumours of blood vessel origin and are classified as capillary, cavernous or central. They appear as flat or raised reddish-blue lesions and are generally solitary, affecting women in younger age groups. The tumour may be slowly progressive, involving extensive portions of the superficial and deep blood vessels, and affect function, depending on location. They are common in the head and neck region but rarely in the oral cavity. Oral lesions generally appear on the lips, buccal mucosa and tongue, but rarely on the palate. As the lesion can be confused with pyogenic granuloma, histopathological examination is important for a final diagnosis. The case presented here signifies a rare location of a capillary haemangioma on the palate in a middle aged man. The lesion was diagnosed by histopathology after surgical excision.